A Study of Effective Demographic Factors in Autism Spectrum Disorder - Amir Bazrafshan; Leila Sadeghi (مجله علوم پزشکی صدرا, 2021)
Introduction: The prevalence of autism spectrum disorder is increasing recently, leading to a decline in individual performance and many problems in the family. The cause of the disease is still unknown. This study aimed to investigate the epidemiological factors in autism disorder in patients referred to psychiatric clinics of Shiraz University of Medical Sciences in 1397 in Shiraz. Methods: This is a descriptive study. A total of 114 children were selected through convenience sampling. Data were collected through questionnaires including maternal information during pregnancy and data related to father and child. Results: The results showed that 54.3% of mothers who were giving birth were in the range of 20-29 years old and 32.1% of fathers were between 30 and 34 years old. 96.4% of parents did not smoke or drink during pregnancy. 66.5% of children were born by cesarean section and 70.8% of infants’ weight were in the range of 2500 to 3999 grams. 75% of mothers did not report pregnancy complications and 51.8% of the mothers had 38-37 weeks gestation. Conclusion: The present study showed that the epidemiological factors in these children were in the normal range and more studies are needed to obtain the causes of this disease.